2021
DOI: 10.3390/diagnostics11020366
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Protoporphyrin Is a Reliable Marker of Functional Iron Deficiency in Patients with Inflammatory Bowel Disease

Abstract: Iron deficiency (ID) is a common manifestation of inflammatory bowel disease (IBD), arising primarily due to chronic inflammation and/or blood loss. There is no gold standard for ID diagnosis, which is often complicated by concomitant inflammation. Zinc protoporphyrin (ZnPP) correlates with parameters of iron homeostasis and has been identified as a promising marker for ID, irrespective of inflammation. We investigated the diagnostic performance of ZnPP in ID, iron deficiency anemia, anemia of chronic disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Different studies have identified ZnPP as a biomarker of IDA which is not or little affected by co-occurring acute inflammations [ 14 , 40 ]. In ACD ZnPP has been shown to detect and quantify derangements of iron metabolism associated with chronic inflammatory disorders and also helps to monitor the success of iron therapy of chronic inflammatory diseases[ 23 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Different studies have identified ZnPP as a biomarker of IDA which is not or little affected by co-occurring acute inflammations [ 14 , 40 ]. In ACD ZnPP has been shown to detect and quantify derangements of iron metabolism associated with chronic inflammatory disorders and also helps to monitor the success of iron therapy of chronic inflammatory diseases[ 23 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many of the biomarkers are not only affected by iron deficiency but also by inflammation; such as ferritin, a well-known acute-phase protein[ 11 13 ]. However, it has been shown that ZnPP is less sensitive to the inflammatory status [ 14 ]. In COVID-19 patients some of the iron markers are affected [ 6 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation